Single-cell Transcriptional Changes in Neurodegenerative Diseases. (15th December 2021) - Ahmadi, Amirhossein; Gispert, Juan D.; Navarro, Arcadi; Vilor-Tejedor, Natalia; Sadeghi, Iman
Highlights: Sex-specific changes observed in AD pathology in neurons and microglia. Dopaminergic neurons revealed marker genes associated with PD. Astrocytic genes altered in the cingulate cortex of Huntington. MS-associated genes showed the highest changes in excitatory neurons. Suppression of HOXA1 and HOXA5 correlates to synaptic dysfunction in ALS. Abstract: In recent decades, our understanding of the molecular changes involved in neurodegenerative diseases has been transformed. Single-cell RNA sequencing and single-nucleus RNA sequencing technologies have been applied to provide cellular and molecular details of the brain at the single-cell level. This has expanded our knowledge of the central nervous system and provided insights into the molecular vulnerability of brain cell types and underlying mechanisms in neurodegenerative diseases. In this review, we highlight the recent advances and findings related to neurodegenerative diseases using these cutting-edge technologies.